Scaling Parameter Dependent Drain Induced Barrier Lowering Effect in Double-Gate Silicon-on-Insulator Metal-Oxide-Semiconductor Field Effect Transistor - Samudra, G. (2014)
Japanese Journal of Applied Physics, Part 1: Regular Papers and Short Notes and Review Papers